Mechanistic Insights into Regulation of JAK2 Tyrosine Kinase - Hubbard, Stevan R. (Frontiers in Endocrinology, 2018)
Janus kinases (JAKs) are non-receptor protein tyrosine kinases that serve as the catalytic signaling components for a wide range of cytokine receptors, including the receptors for interleukins, interferons, growth hormone, erythropoietin, and leptin (1). There are four mammalian members of the JAK family: JAK1–3 and TYK2 (tyrosine kinase-2), which are constitutively bound to the cytoplasmic region of cytokine receptors. In general, binding of cytokines to the extracellular region of their cognate receptors induces receptor dimerization, facilitating trans-phosphorylation (activation) of the associated JAKs. Typically, the dimerized receptor chains are distinct (e.g., interferon- receptors 1 and 2) and harbor two different JAK molecules (e.g., JAK1 and TYK2) (2). Cytokine receptors belonging to a subclass that includes erythropoietin receptor (EpoR) and growth hormone receptor (GHR) are homodimeric and bind JAK2 exclusively. For these receptors, it is not entirely clear whether they are dimerized by cytokine or exist as pre-formed, inactive dimers that undergo a cytokine-induced structural rearrangement. Activated JAKs phosphorylate specific tyrosine residues on the cytokine receptors and subsequently on STAT (signal transducer and activator of transcription) proteins (3), which are recruited to the phosphorylated receptors through their SH2 (Src-homology 2) domains. Phosphorylated STATs then translocate to the nucleus to initiate specific transcriptional programs. JAK-STAT signaling pathways are critical for organismal development and homeostasis, particularly in immunity (1, 3). JAKs possess four structural domains (Figure 1A): an N-terminal FERM (band 4.1, ezrin, radixin, moesin) domain, an SH2-like (SH2L) domain, a kinase-like or pseudokinase domain (JH2 [Janus homology-2]), and a C-terminal tyrosine kinase domain (JH1). The FERM and SH2L domains form a single structural unit that engages the so-called Box1 and Box2 cytoplasmic regions of cytokine receptors (4) (Figure 1B). The SH2L domain of JAKs binds, in its aberrant phosphotyrosine-binding pocket (5), a glutamate residue in the Box2 region of the receptor (4, 6). As far as is known, receptor binding and specificity are determined solely by the FERM and SH2L domains of JAKs, although the specificity determinants are not fully understood (7). While homozygous loss-of-function mutations in JAK genes can be lethal (JAK1 and JAK2), or highly debilitating (JAK3, severe combined immunodeficiency), heterozygous